DOCETAXEL VERSUS DOCETAXEL PLUS CAPECITABINE AS NEOADJUVANT CHEMOTHERAPY FOR TRIPLE-NEGATIVE BREAST CANCER PATIENTS - KHAN , RAA; MASOOD , AI; KHAN , S; MASOOD , A; ABDULMANAN, .; ZULFIQAR , A (Biological and Clinical Sciences Research Journal, 2024)
Triple-negative breast cancer (TNBC) poses a significant risk of metastasis and relapse, demanding effective neoadjuvant chemotherapy strategies. This retrospective study aimed to compare the outcomes of a sole docetaxel versus a docetaxel and capecitabine combination (TX) regimen as a neoadjuvant treatment for triple-negative breast cancer. The current retrospective analysis was conducted at the oncology department of Nishtar Hospital Multan and encompassed 80 randomly assigned female patients with triple-negative breast cancer between September 17, 2021, and December 31, 2022. They were further divided into two groups. The TX regimen (docetaxel 75 mg/m2 d1 with capecitabine 800 mg/m2 twice d1-14, q3w) was given to forty patients in the first group named the TX group, where the T regimen (docetaxel 75 mg/m2 d1 q3w) was given to other forty patients assigned in the second group called as T group, over four cycles. The primary endpoint was achieving a pathological complete response (pCR) in the breast, with secondary objectives including pCR in both the breast and axilla, invasive disease-free survival (iDFS), overall 0ne year survival (OS), and safety assessments. In the retrospective analysis, 21 patients in the TX group and 5 in the T group achieved pCR (52.5% vs. 12.5%, p=0.014), demonstrating a statistically significant superiority of the TX regimen. The TX regimen substantially increased pCR incidence (95% CI 2.3-47.1%; p = 0.028) within a subgroup characterized by a high Ki-67 level. The TX group showed a higher incidence of hand-foot syndrome and a statistically insignificant (p > 0.05) incidence of alopecia, presenting a manageable toxicity profile. Comparable iDFS and OS rates were observed in both groups throughout the 12-month average follow-up period. This retrospective analysis indicates that the TX regimen yielded significantly superior results, with a marked increase in pCR rates, particularly in the high Ki-67 subgroup. The observed toxicity profile was manageable, emphasizing the clinical benefits of incorporating capecitabine with docetaxel in neoadjuvant chemotherapy for triple-negative breast cancer patients.